2022
DOI: 10.3389/fmicb.2021.827799
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Severe Acute Respiratory Syndrome Coronavirus 2 Isolates From Central Inner Sardinia

Abstract: BackgroundThe SARS-CoV-2 pandemic stimulated an outstanding global sequencing effort, which allowed to monitor viral circulation and evolution. Nuoro province (Sardinia, Italy), characterized by a relatively isolated geographical location and a low population density, was severely hit and displayed a high incidence of infection.MethodsAmplicon approach Next Generation Sequencing and subsequent variant calling in 92 respiratory samples from SARS-CoV-2 infected patients involved in infection clusters from March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Deletions, insertions, frameshift variants, and up/downstream variants were much rarer. This observation is also in line with the finding of Malune et al, whose study reported less than 10% of these mutations [70].…”
Section: Discussionsupporting
confidence: 93%
“…Deletions, insertions, frameshift variants, and up/downstream variants were much rarer. This observation is also in line with the finding of Malune et al, whose study reported less than 10% of these mutations [70].…”
Section: Discussionsupporting
confidence: 93%
“…A possible reason is the dissociation of polymerase complex, now that these viruses present a high rate of RNA recombination during replication [ 19 , 22 ]. Nevertheless, some next-generation sequencing (NGS) approaches have analyzed the evolution of lineages in this short period of time, identifying an increasing number of mutations and variability in S and N proteins, but more conserved sequences in RdRp [ 23 ]. Importantly, these mutations can lead to an enhanced replication and transmissibility of the virus, and in turn this can favor further mutations, thus explaining the success and rapid evolution of SARS-CoV-2 [ 24 ].…”
Section: A General Perspective For Sars-cov-2mentioning
confidence: 99%
“…The rapid evolution has shown that many ramifications can arise from the same lineage; for example, the Delta variant has produced approximately 200 subvariants, and Omicron has 4 prominent subvariants with great spreading ability. As previously mentioned, most common mutations that can be found are within S and N proteins [ 23 ].…”
Section: Main Sars-cov-2 Variantsmentioning
confidence: 99%
“…It is, therefore, not surprising that Sardinia was one of the last Italian regions infected during the first wave (March–May 2020), with one of the lowest COVID-19 cases incidences reported at that time (79.9 cases/100,000 inhabitants). Furthermore, its socio-geographic features—insularity, large rural areas, limited connectivity between major cities and low population density—have created a peculiar epidemiological scenario [ 13 , 17 , 19 , 20 ]. Tourism flow to the island during the summer season (June–September 2020) was restored after the lockdown measures, causing a sharp increase in the number of infections, and during the second wave Sardinia became the first Italian region categorized as high risk by the European Centre for Disease Prevention and Control (ECDC) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%